Porphyria Cutaneous Tarda versus Pseudoporphyria Cutaneous Tarda in a hemodialysis patient. Case presentation - Eliseo Capote Leyva (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Porphyria cutanea tarda (PCT) is a relatively common disease. It is the result of the functional deficiency of an enzyme called uroporphyrinogen decarboxylase. In patients on intermittent periodic hemodialysis, it is described a similar clinical situation called late cutaneous pseudoporphyria. The case of a patient in intermittent periodic hemodialysis for 5 years is presented. The patient has C virus liver disease that develops bullous lesions on the skin exposed to the sun, and had an adequate response to the indicated therapy (based on the restriction of iron use, in a more effective use of erythropoietin, periodic phlebotomies of low volume and protection from solar radiation). The lesions disappeared with the medical measures taken to improve the patient's quality of life.